Fungicolous fungi on microscopic fungi parasitic to the vegetation of the urban environment - Ewa Sucharzewska; Elżbieta Ejdys; Dariusz Kubiak (Acta Mycologica, 2023)
The research aimed to study the extent of fungicolous fungi prevalence on the thallus of fungi parasitic to the plants of the urban environment and to assess the species diversity of these microorganisms, with particular attention paid to the phenomenon of hyperparasitism. The research material consisted of herbaceous plants, trees, and shrubs showing signs of infestation by fungi, planted as park plants, along communication arteries, for hedges or ornamental plants, collected in larger cities of north-eastern Poland. Macroscopic and microscopic analysis revealed the presence of 12 different species of fungicolous fungi. The greatest diversity was found on the parasite of Alcea rosea , i.e., Puccinia malvaceraum , on which four fungal species were recorded. Four species of hyperparasites were identified: Ampelomyces quisqualis on the thallus of 19 Erysiphales species , Cladosporium uredinicola on the thallus of 5 species of the Pucciniales order, Clonostachys epichloë on Epichloë typhina , and Sphaerellopsis filum on the thallus of 11 representatives of Pucciniales. The study was also the first to record the presence of superparasites: Ampelomyces quisqualis on four Erysiphales species and Sphaerellopsis filum on three Pucciniales species. It is difficult to determine the relationships established by the other identified fungicolous fungi due to the lack of literature data. Nevertheless, the study demonstrated the presence of, among others, Stemphylium sarciniforme structures inside Erysiphe palczewskii appendages and the absence of ascospores inside the fruiting bodies indicative of the invasive nature of this relationship. However, confirmation of these findings requires further detailed microscopic and molecular analyses.